2008
DOI: 10.1021/jp803314c
|View full text |Cite
|
Sign up to set email alerts
|

Water in Acid Boralites: Hydration Effects on Framework B Sites

Abstract: Properties and behaviour of protonated boron-containing zeolites at different hydration degree have been investigated by means of periodic DFT approaches. Geometry optimization and room-temperature Car-Parrinello molecular dynamics results, in line with experimental findings, indicate that the BO 3-bound silanolic acid site typical of dry boralites should convert to a solvated H 3 O + hydrogen bonded to tetrahedral BO 4 at moderate water content. By increase of the water loading, the tetrahedral structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…For instance, boron zeolites are less acidic than Al‐ones due to the tendency of boron to be trigonal . The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal,, whereas tetrahedral boron geometry is recovered upon hydration . Such weaker Brønsted acidity of B‐sites guarantees a high selectivity for ethylene from methane and is relevant for the environmentally friendly production of styrene .…”
Section: Empty Space Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, boron zeolites are less acidic than Al‐ones due to the tendency of boron to be trigonal . The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal,, whereas tetrahedral boron geometry is recovered upon hydration . Such weaker Brønsted acidity of B‐sites guarantees a high selectivity for ethylene from methane and is relevant for the environmentally friendly production of styrene .…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…[236][237][238] The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal, [237,239] whereas tetrahedral boron geometry is recovered upon hydration. [240][241][242] Such weaker Brønsted acidity of B-sites guarantees a high selectivity for ethylene from methane [243] and is relevant for the environmentally friendly production of styrene. [244] Aluminophosphates (ALPO) [245,246] generally have neutral framework and large pore sizes, like in VPI-5.…”
Section: Chemical Aspectsmentioning
confidence: 99%
“…The experimental work as reviewed by Millini et al [1] and further performed by means of 11 B solid-state NMR [10,11] and IR spectroscopy [12], along with theoretical studies [13][14][15] have shown that the boron change in coordination upon heating is strongly related to the nature of the counterions (protons, large counterions, cationic organic structure directing agent (SDA)) and to the hydration/dehydration level. In particular, in fully hydrated proton forms, boron is tetrahedrally coordinated, whereas upon dehydration boron assumes a trigonal coordination [10,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…Removal of organic complexes from the zeolite pores by template burning leaves behind one proton per each SDA complex for charge-balancing and hence boron atoms are transformed to trigonally coordinated boron. This tetrahedral-to-trigonal boron conversion is fully reversible upon rehydration [10][11][12]15,16,19]. The questions remain as to whether the boron atoms with trigonal coordination are in non-framework positions, or anchored in the framework [10].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Host-guest systems are applicable in various fields, such as ion exchange, catalysis, sensing, and supramolecular organization. [9][10][11][12][13][14] These widespread applications of zeolites are mainly attributed to their catalytic activity, [15][16][17][18][19] which is mainly due to the presence of Brønsted acid/base sites. The acid/base sites of zeolites are capable of adsorbing guest molecules by strong hydrogenbonding interactions and lead to protonation or deprotonation of the guest molecules.…”
Section: Introductionmentioning
confidence: 99%